Função sexual em usuárias de métodos contraceptivos reversíveis de longa duração - Matos, Beatriz Nery De [UNIFESP] (2020)
This study’s aim is to identify the possible impacts of the contraceptive methods LARC (long acting reversible contraception) (DIU Cu) or levonorgestrel releaser (DIU-LNG) and subcutaneous implant) in the female sexual function. It is a comparative study, prospective not randomized in women attended at the Family Planning ambulatory on Escola Paulista de Medicina – UNIFESP in São Paulo, taken before the LARC method insertion and 6 months later. It envolved 120 women aged 18 to 50 years, all fertile women, sexually active, of single partner, whom informed to have had sexual relation in the 4 weeks prior to the study. For the data collection, a questionnaire with sociodemographic information was used, as well as the female sexual function index translated to Portuguese in Brasil and a questionnaire about the contraceptive method satisfaction by the Likert scale. The analysis were made using Excel and a statistic software called R, the tests of Wilcoxon, Kruskal-Wallis and Bonferroni were also used. Results: Group 1 had women who used DIU Cu, group 2 used subcutaneous implant and group 3 DIU-LNG, all the three with 40 women each whom filled up the questionnaire, on all the groups most of them were aged 18 to 26 years - 42,5% at group 1, 63,4% at group 2 and 52,5% at group 3. The FSFI global average presented significant differences after the copper DIU insertion (p=0,0023) on the domains: desire, excitation and orgasm, on the DIU-LING (p=0,0363) on the domains: desire and excitation. The FSFI global average after the subcutaneous implant insertion did not present significant differences (p=0,2641). On the satisfaction method questionnaire of Likert, the group 3 presented highest average in all the analyzed variables. Concludes that the intrauterine devices presented positive impact on the female sexual function, while the subcutaneous did not present any variation on the sexual function. However, new studies are necessary to investigate the long term impact of these methods, inquiring if this improve on the sexuality will keep up over the years as well as to investigate the side effects that may cause a dissatisfaction with these methods.